AN ANALYSIS OF STUDENTS’ ABILITY IN USING SUB-ORDINATE CONJUNCTION IN SENTENCE WRITING OF THE GRADE XII STUDENTS OF SMA N 2 METRO ACADEMIC YEAR 2013/2014 - Bambang Eko Siagianto (Premise: Journal of English Education and Applied Linguistics, 2014)
Abstracts: Sub-ordinate conjunction is very confusing to comprehend by students. In using sub-ordinate conjunction, students usually had errors. The purpose of this research to analyze whether or not the students are able to use sub-ordinate conjunction in sentence writing, to classify kinds of sub-ordinate conjunction that was often misused by students in sentence writing The research was done at the grade XII of SMA N 2 Metro in second semester of the academic year 2013/2014. The predicted research findings are; the students cannot divide or difference the type of sub-ordinate conjunction well, and they often errors using it in sentences.The result of the students test in using sub-ordinate conjunction in sentence writing proves that most of the students at the grade XII of SMA N 2 Metro used the list of words “after, then, when, because” on their sentence writing. The students found these words easier to be used as conjunction especially sub-ordinate conjunction in their sentence writing than other conjunction. While, for other list of words doesn’t used by the students because the students cannot adapted the words in their sentence writing. The most familiar sub-ordinate conjunction seems to be  “before and since” (each of them is gained by 22 students = 91,6%), but the students are unfamiliar with the other words in sub-ordinate conjunction mainly “till and unless” (each of the is gained by 13 students = 54,1%). The other sub-ordinate conjunctions are quite familiar for them.